2016
DOI: 10.5539/ijef.v8n2p115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Quantile Panel Data Analysis of Stock Returns Predictability

Abstract: <p>This paper analyses the effect of financial ratios on stock returns using quantile regression for dynamic panel data with fixed effects. Eighty three firms of manufacturing industry, which were traded on the Borsa Istanbul for 2000-2014 period, are covered in the study. The most of financial variables have heterogeneous structure so they generally include extreme values. Thus, panel quantile regression technique, suggested by Koenker (2004), is used. Since the technique yields robust estimator in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, due to the influence of bubbles on asset pricing, this study could be extended by employing a present value model that is adjusted to the presence of bubbles which warrants the use of a regime-switching model that incorporates bubbles as previously done by McMillan (2010). Lastly, future studies could further disaggregate the data and assess the predictive ability of financial statement information using firmlevel panel data as done by Güloğlu et al (2016) and Alexakis et al (2010), among others. You are free to: Share -copy and redistribute the material in any medium or format.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, due to the influence of bubbles on asset pricing, this study could be extended by employing a present value model that is adjusted to the presence of bubbles which warrants the use of a regime-switching model that incorporates bubbles as previously done by McMillan (2010). Lastly, future studies could further disaggregate the data and assess the predictive ability of financial statement information using firmlevel panel data as done by Güloğlu et al (2016) and Alexakis et al (2010), among others. You are free to: Share -copy and redistribute the material in any medium or format.…”
Section: Discussionmentioning
confidence: 91%
“…Alexakis et al (2010) found that valuation ratios, asset utilisation, debt, investment and liquidity ratios could predict stock returns of 47 non-financial firms on the Athens stock market. Güloğlu et al (2016) showed that financial leverage, dividend yield and market-to-book ratios could predict stock returns of 83 Turkish firms. Kheradyar et al (2011) found that dividend yield, earnings yield and book-to-market ratios could predict returns of 960 companies on the Malaysian Stock Exchange.…”
Section: Valuation Ratios and Predictability Of Returns In International Marketsmentioning
confidence: 99%
“…Quantile regression models allow the researcher to account for unobserved heterogeneity and heterogeneous covariates effects, while the availability of panel data potentially allows the researcher to include fixed effects to control for some unobserved covariates (Canay, 2011). Recently, some researchers associated these two methodologies and named it Panel Quantile Regression (Koenker, 2004;Geraci and Bottai, 2007;Abrevaya and Dahl, 2008;Galvao, 2008;Rosen, 2009;Lamarche, 2010;Guloglu, et al 2016). Koenker (2011) explains the panel quantile regression with fixed effect like these: suppose that the conditional quantile functions of the response of the j th observation on the i th individual y ij takes the form:…”
Section: Methodsmentioning
confidence: 99%